STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH PESERTA DIDIK - Maisyanah, Maisyanah; Syafa'ah, Nailusy; Fatmawati, Siti (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
All educational institutions try to form students who have faith and noble character. In this case the teacher has a central role to participate in the process, especially for Islamic education teachers. In the teaching and learning process not only provides knowledge, but must show aspects of educating morals to students. Therefore the strategy that is owned by the teacher in forming moral character must be appropriate so that the learning process is more effective and efficient. The purpose of this study was to determine the values ​​of moral values ​​implanted by Islamic education teachers at and to find out the strategies used by Islamic education teachers in shaping students' morals. This study uses a descriptive qualitative approach with methods of literature. The results of this study indicate that the formation of morals by Islamic education teachers is by maintaining cleanliness, caring for others and being responsible for what has been done. While the strategy used by Islamic education teachers in shaping the morals of students is by giving examples to students and accustoming Dhuha prayer and Dhuhr prayer in congregation, and reading the Qur'an together so that students have noble character.